2021
DOI: 10.1007/s11682-021-00493-w
|View full text |Cite
|
Sign up to set email alerts
|

Left egocentric neglect in early subacute right-stroke patients is related to damage of the superior longitudinal fasciculus

Abstract: A typical consequence of stroke in the right hemisphere is unilateral spatial neglect. Distinct forms of neglect have been described, such as space-based (egocentric) and object-based (allocentric) neglect. However, the relationship between these two forms of neglect is still far from being understood, as well as their neural substrates. Here, we further explore this issue by using voxel lesion symptoms mapping (VLSM) analyses on a large sample of early subacute right-stroke patients assessed with the Apples C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, biomarkers and neuroimaging tests are needed to understand the plasticity mechanisms in USN patients to help select the best candidates for neuromodulation interventions. Some authors reported that lesions in the superior longitudinal fasciculus might cause persistent USN, and the evaluation by diffusion tensor imaging studies can provide direct evidence of anatomical localization of brain function for a better response after brain stimulation 34–36 . However, no biomarkers have been validated in stroke patients with USN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, biomarkers and neuroimaging tests are needed to understand the plasticity mechanisms in USN patients to help select the best candidates for neuromodulation interventions. Some authors reported that lesions in the superior longitudinal fasciculus might cause persistent USN, and the evaluation by diffusion tensor imaging studies can provide direct evidence of anatomical localization of brain function for a better response after brain stimulation 34–36 . However, no biomarkers have been validated in stroke patients with USN.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that lesions in the superior longitudinal fasciculus might cause persistent USN, and the evaluation by diffusion tensor imaging studies can provide direct evidence of anatomical localization of brain function for a better response after brain stimulation. [34][35][36] However, no biomarkers have been validated in stroke patients with USN. Therefore, future efforts should compare optimal intervention strategies according to individual characteristics before larger and more comprehensive trials can be planned.…”
Section: Discussionmentioning
confidence: 99%
“…The superior longitudinal fasciculus links the frontal cortex with the temporal, parietal, and occipital lobes and plays a major role in language, attention, memory, and emotions (44). Previous studies have demonstrated that damage to the superior longitudinal fasciculus is consistently found in patients with USN following stroke (15,16,45). Moreover, different loci of the involved superior longitudinal fasciculus were suggested to have a role in diverse USN phenotypes (46).…”
Section: Discussionmentioning
confidence: 99%
“…white matter attention networks, specifically in the frontalparietal superior longitudinal fasciculus, and some association with interhemispheric disconnections as well [2]- [5]. Some research has also correlated lesions in the ventral frontal lobe, right inferior parietal lobe or superior temporal lobe to the manifestation of SN [6], [7].…”
mentioning
confidence: 99%